Peran Orang Muda Katolik Dalam Hidup Menggereja Di Stasi Santo Fransiskus Xaverius Kole - Kristina Rina Pataloan; Reniyanti Lombe; Anita Ruru (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2025)
The purpose of this research is to describe the role of OMK in the station of St. Francis Xaverius Kole. The research was conducted in relation to the presence of OMK which is a major force in the Church. They have participated in church life since their youth, which is synonymous with a time of vigor. They are not only referred to as the future of the Church which makes it seem as if young people will play a role in the Church when their youthfulness is lost due to age, but it is precisely in their youthful enthusiasm that young people provide wealth for the Church through their involvement in church life which is manifested in the implementation of the five pillars of the Church, namely kerygma (proclamation), koinonia (fellowship), lituria (sanctification), diakonia (service) and martyria (witness) which manifest the existence of the Church as a community of faith in the world. The results of the study found that young Catholics in Kole Station, although not too many of them, still play a role in church life in accordance with their respective ways. This research uses qualitative methods, namely interviews with several informants to obtain more in-depth data about the facts that occur in the field.